Combination checkpoint inhibitor therapy induces multiple immune major related adverse events in the treatment of vaginal melanoma: A cautionary case report - T. Graham Norwood; Michelle J. Wang; Warner K. Huh (Elsevier, 2019)
Background: Immune checkpoint inhibitors (ICI) eliminate cancer cells through release of inhibition of cytotoxic CD8+ lymphocytes. Potent systemic activation of immune cells provides unprecedented efficacy in some types of advanced cancer therapy, but also often induces serious immune related adverse events (irAEs) that can be devastating if not promptly identified and properly managed. Herein, we describe the case of multiple major irAEs manifesting after administration of combination ICI therapy in a patient with vaginal melanoma.Case:A 54-year-old, G2P0 woman with recurrent metastatic vaginal melanoma, following three doses of combination nivolumab-ipilimumab immunotherapy, presented for admission at our tertiary care center for the work-up of sudden-onset of colitis of unknown etiology. Prior to admission at our facility, the patient was diagnosed with a severe maculopapular rash, headaches and hyponatremia in the weeks immediately following initiation of therapy. During work up of the colitis, infectious etiologies were ruled out, and the patient was discharged on a steroid taper for treatment of presumed immune-related colitis. Consideration of salt-supplement resistant hyponatremia with new onset frontal headache in the setting of immune-related colitis indicated possible hypophysitis. With high suspicion for multiple high grade irAEs, ICI was discontinued, and the patient was given high dose intravenous steroids prior to discharge with a prednisone dose taper for outpatient management. After control of irAEs was achieved, ipilimumab therapy was subsequently discontinued to minimize the chance of recurrent irAEs, yet nivolumab monotherapy was resumed in an attempt to control disease progression that could occur in with iatrogenic immunosuppression. Conclusion: ICIs have demonstrated the ability to induce improved long-term survival in metastatic cutaneous or mucosal melanomas, including those of gynecologic origin. As ICI therapy becomes more widespread, healthcare providers across all fields of medicine need be vigilant to recognize the symptoms of irAEs that can often masquerade as common illnesses to prevent potentially dangerous irreversible immune toxicities. Keywords: Immunotherapy, Immune toxicity, Immune-related adverse events, Melanoma